Fluency and rule breaking behaviour in the frontal cortex. (3rd February 2020) - Cipolotti, Lisa; Molenberghs, Pascal; Dominguez, Juan; Smith, Nicola; Smirni, Daniela; Xu, Tianbo; Shallice, Tim; Chan, Edgar
Abstract: Design (DF) and phonemic fluency tests (FAS; D-KEFS, 2001) are commonly used to investigate voluntary generation. Despite this, several important issues remain poorly investigated. In a sizeable sample of patients with focal left or right frontal lesion we established that voluntary generation performance cannot be accounted for by fluid intelligence. For DF we found patients performed significantly worse than healthy controls (HC) only on the switch condition. However, no significant difference between left and right frontal patients was found. In contrast, left frontal patients were significantly impaired when compared with HC and right frontal patients on FAS. These lateralization findings were complemented, for the first time, by three neuroimaging; investigations. A traditional frontal subgrouping method found significant differences on FAS between patients with or without Left Inferior Frontal Gyrus lesions involving BA 44 and/or 45. Parcel Based Lesion Symptom Mapping (PLSM) found lower scores on FAS were significantly associated with damage to posterior Left Middle Frontal Gyrus. An increase in rule break errors, so far only anecdotally reported, was associated with damage to the left dorsal anterior cingulate and left body of the corpus callosum, supporting the idea that conflict resolution and monitoring impairments may play a role. Tractwise statistical analysis (TSA) revealed that patients with disconnection; in the left anterior thalamic projections, frontal aslant tract, frontal; orbitopolar tract, pons, superior longitudinal fasciculus I and II performed significantly worse than patients without disconnection in these tracts on FAS. In contrast, PLSM and TSA analyses did not reveal any significant relationship between lesion location and performance on the DF switch condition. Overall, these findings suggest DF may have limited utility as a tool in detecting lateralized frontal executive dysfunction, whereas FAS and rule break behavior appears to be linked to a set of well localized left frontal grey matter regions and white matter tracts. Highlights: Performance on fluency tasks is not underpinned by fluid intelligence. Design fluency (DF) from the D-KEFS has limited clinical utility. Left BA 44/45 and left white matter network underpin Phonemic fluency (FAS). FAS rule breaks related to left dorsal ant. cingulate and corpus callosum damage.